Risk Factors That Influence the Incidence of Stunting Reviewed from Pregnancy History Bululawang Health Center Area - Wahyuni, Candra; Erma Retnaningtyas; Komariah Tusolikah (Journal of Global Research in Public Health, 2017)
Efforts to indirectly prevent stunting incidents, namely through sensitive intervention efforts, are various development activities outside the health sector targeting the general public, activities include providing clean water, various poverty alleviation efforts, food and nutrition security, and others. The incidence of stunting at Bululawang Health Center reached 15.32% while in Krebet Village it was 15.13%. Based on the increasing incidence of stunting at Bululawang Health Center, researchers are interested in examining the risk factors that influence the incidence of stunting in terms of pregnancy history at Tunas Bangsa PAUD, Krebet Village, Bululawang Health Center work area.The research design uses correlational analytics with a cross-sectional approach.Population All mothers who have children at Paud Tunas Bangsa, Krebet Village, Bululawang Health Center Working Area, purposive sampling technique. The independent variables in this study are Risk Factors, while the dependent variable is stunting. Data analysis using the Chi Square testThe results of the study obtained testing of risk factors affecting stunting in toddlers are the Asymp. Sign value <0.05. Based on the table above, the value that is <0.05 is questions 2,3, 4. It is interpreted that there are 3 risk factors during pregnancy that affect stunting in toddlers. While the other 4 factors in the questionnaire do not affect stunting in infants.Based on the results of research and discussion on risk factors that influence stunting during pregnancy at Bululawang Health Center on May 12, - May 18, it can be concluded as follows: Respondents were 30 people, with the characteristics of toddler respondents who were indicated as stunting as many as 11 toddlers and risk factor analysis as many as 7 questions. The test results used the chi-square method on each risk factor for stunting indications with a significance level of 0.05. The results showed that Lila, Anemia, and Pregnancy Complications were risk factors that influenced the incidence of stunting at Bululawang Health Center.